Salmon louse (Lepeophtheirus salmonis (Krøyer)) control methods and efficacy in atlantic salmon (Salmo salar (Linnaeus)) aquaculture: A literature review - Cerbule, Kristine; Godfroid, Jacques (Fishes, 2020)
The salmon louse ( Lepeophtheirus salmonis ) causes problems in Atlantic salmon ( Salmo salar ) aquaculture in the Northern Hemisphere, because infestations can result in both a loss of production and in fish mortality. Several types of treatment have been used to control louse infestations, but these have seen varying success. The aim of this review is to examine the efficacy and safety of commonly used treatments (chemical, biological, mechanical, and preventive measures) as documented in peer-reviewed publications. Efficacy is assessed in relation to a reduction in numbers of lice, and safety is assessed as a lack of negative treatment-associated effects on fish health and welfare (Atlantic salmon and/or cleaner fish). Most chemical treatments showed decreasing efficacy over time, together with the use of increasing concentrations as a result of the development of resistance to the treatments by lice. The need for a restrictive use of pesticides to preserve treatment efficacy has been emphasized. The use of cleaner fish was suggested to be effective, with few or no negative effects towards Atlantic salmon. The use of cleaner fish would be preferable to chemical treatment if the farmed fish health and welfare criteria are met. At present, the number of peer-reviewed publications relating to other forms of treatment and prevention are sparse.